Economies of Africa and Asia in the inter - war depression/ edited by Ian Brown - "Brown, Ian (ed.)" (London, 1989)
The essays in this volume were originally presented at a conference held at a school of oriental and African Studies, University of London, in December 1985. I am very grateful to the Economic and Social Research Council, the Nuffield Foundation, the British Council and the School of oriental and African Studies of financing that conference so generously. The school has also provided the funds which now bring the papers to publication.
Keywords: Economic development